2002
DOI: 10.1021/jf011485t
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol 4-β-d-Glucoside, an Important Phenolic Compound in Olive Fruits and Derived Products

Abstract: There is increasing interest in olive polyphenols because of their biological properties as well as their contribution to the color, taste, and shelf life of olive products. However, some of these compounds remain unidentified. It has been shown that hydroxytyrosol 4-beta-D-glucoside (4-beta-D-glucosyl-3-hydroxyphenylethanol) coeluted with hydroxytyrosol [(3,4-dihydroxyphenyl)ethanol] under reversed phase conditions in the phenolic chromatograms of olive pulp, vegetation water, and pomace of olive oil processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
143
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(153 citation statements)
references
References 18 publications
7
143
1
2
Order By: Relevance
“…Oleuropein, an ester of elenolic acid and hydroxytyrosol, identified as a major phenolic compound of OMWW (Dermeche et al, 2013;Visioli et al, 2002;Romero et al, 2002), was identified by its molecular ion at m/z 539 and by the presence of the hydroxytyrosol (m/z 153) ion fragment, only in the extracts derived from mountainous areas whereas we failed to identify this compound in the plain areas extracts. Oleuropein in these extracts had probably degraded into elenolic acid and hydroxytyrosol by an esterase during the mechanical olive oil extraction process .…”
Section: Secoiridoidsmentioning
confidence: 58%
“…Oleuropein, an ester of elenolic acid and hydroxytyrosol, identified as a major phenolic compound of OMWW (Dermeche et al, 2013;Visioli et al, 2002;Romero et al, 2002), was identified by its molecular ion at m/z 539 and by the presence of the hydroxytyrosol (m/z 153) ion fragment, only in the extracts derived from mountainous areas whereas we failed to identify this compound in the plain areas extracts. Oleuropein in these extracts had probably degraded into elenolic acid and hydroxytyrosol by an esterase during the mechanical olive oil extraction process .…”
Section: Secoiridoidsmentioning
confidence: 58%
“…Haugh unit = 100 × log (AH + 7.57-1.7 × EW 0.37 ), where AH = albumen height and EW = egg weight. A colorimeter (Minolta Chromameter CR 400; Minolta Co., Osaka, Japan) to assess the egg yolk colour and the CIELAB colorimetric (Romero et al, 2002). Eggshell breaking strength was measured using a cantilever system by applying increased pressure to the broad pole of the shell using a Force Reader instrument (Orka Food Technology Ltd, Ramat Hasharon, Israel).…”
Section: Methodsmentioning
confidence: 99%
“…Phenolic compounds were extracted beforehand [14] and measured at 725 nm by spectrophotometry using the Folin-Ciocalteau method [9].…”
Section: Methodsmentioning
confidence: 99%